Prarancangan Pabrik High Fructose Syrup Dari Tepung Tapioka Kapasitas Produksi 110.000 Ton/Tahun - Widuri, Hasri; , Eni Budiyati, S.T.,M.Eng; , Rois Fatoni, S.T.,M.Sc.,Ph.D (2016)
High fructose syrup is often used as a sweetener in the food industry, for example in the candy industry, jelly, canned fruit and ice cream as a substitute for cane sugar (sucrose). The raw material used in pre-design of high fructose syrup plant is a starch with production capacity of 110,000 tons/year. This plant was planned to be built in 2016 in Lampung Province. High fructose syrup is made through a process of hydrolysis using multy-enzyme catalyst. The α -amylase and Gluco-amylase enzymes will break down molecules of tapioca starch and convert it into glucose in the saccharification reaction, then glucose is converted to fructose by the enzyme Gluco-isomerase, this process called isomerization. The final stage of this process is evaporation to produce HFS-42. The raw material used in this process as much as 88450.307 tons/year of tapioca starch, 27.586 tons/year of CaCl2, 57.402 tons/year of α-amylase, 1,923 tons/year of Gluco-amylase, 0.581 tons / year of HCl, 13.690 tons/year of MgSO4.7H2O, 0.0027 ton / year of NaOH, 11.265 tons / year of Gluco-isomerase, 0,005 tons/year of Polystyrene phosponate and 0.352 tons/year of Polyamine epoxy. Pre-design of high fructose syrup plant obtained the results of economic analysis of total capital investment (TCI) Rp 117,059,063,284.00 and Production Cost Rp 1.276.504.224.148,00. Then for feasibility analysis is return on investment (ROI) before tax of 35.83% and after tax of 25.08%. Pay Out Time (POT) before tax for 2.18 years and after tax for 2.85 years. Break Even Point (BEP) of 42.12%, Shut Down Point (SDP) of 21.02% and the Discounted Cash Flow (DCF) of 34.22%. From the evaluation it can be concluded that the pre-design of High Fructose Syrup plant was established because it has met the standard requirements of the manufacturing.